What's wrong, little Pookie? - Boynton, Sandra (New York : Robin Corey Books, 2007)
Mother tries to find out why little Pookie is upset.
On board pages.
Keywords: Mother and child -- Juvenile fiction; Behavior -- Juvenile fiction; Stories in rhyme; Board books